UPAYA GURU PAI DALAM MENGATASI KESULITAN BACA TULIS HURUF HIJAIYAH PADA ANAK BERKEBUTUHAN KHUSUS - Hamdanah Hamdanah (Jurnal Anak Bangsa, 2023)
The purpose of this study is for students to recognize hijaiyah letters, so that students will find it easier to learn to read and write verses of the Al-Qur'an. The purpose of this research is to find out the efforts of PAI teachers in overcoming difficulties in reading and writing hijaiyah letters in children with special needs at SD SKH Al-Ghisafa Labuan and to find out the inhibiting and supporting factors of Islamic education teachers in overcoming difficulties in reading and writing hijaiyah letters in children with special needs in SKH Al -Ghisafa Labuan. This research is a qualitative research type with a descriptive approach, checking the validity of the data is done by extending the observation and triangulation of the data. Data collection techniques were carried out by means of observation, interviews, documentation and literature study. The research informants are school principals and Islamic religious education teachers. The results of this study are as follows: Learning to read and write hijaiyah letters at SKh Alghisafa Labuan uses the Iqra' learning method. The material taught to children with mental retardation is flexible or adapts to students' abilities. AT SKH Alghisafa, the average mentally retarded child is still in the Iqra' stage. The efforts of PAI teachers in overcoming hijaiyah literacy difficulties for children with special needs are: Carrying out hijaiyah reading and writing activities on Monday and Friday mornings before studying, using various learning methods and the teacher asking parents to teach hijaiyah letters to students. her son at home